Influence of the iron source on the solar photo-Fenton degradation of different classes of organic compounds - Nogueira, RFP; Silva, MRA; Trovo, A. G. (Elsevier B.V., 2005)
In this work the influence of two different iron sources, Fe(NO3)(3) and complexed ferrioxalate (FeOx), on the degradation efficiency of 4-chlorophenol (4CP), malachite green, formaldehyde, dichloroacetic acid (DCA) and the commercial products of the herbicides diuron and tebuthiuron was studied. The oxidation of 4CP, DCA, diuron and tebuthiuron shows a strong dependence on the iron source. While the 4CP degradation is favored by the use of Fe(NO3)(3), the degradation of DCA and the herbicides diuron and tebuthiuron is most efficient when ferrioxalate is used. on the other hand, the degradation of malachite green and formaldehyde is not very influenced by the iron source showing only a slight improvement when ferrioxalate is used. In the case of formaldehyde, DCA, diuron and tebuthiuron, despite of the additional carbon introduced by the use of ferrioxalate, higher mineralization percentages were observed, confirming the beneficial effect of ferrioxalate on the degradation of these compounds. The degradation of tebuthiuron was studied in detail using a shallow pond type solar flow reactor of 4.5 L capacity and 4.5 cm solution depth. Solar irradiation of tebuthiuron at a flow rate of 9 L h(-1), in the presence of 10.0 mmol L-1 H2O2 and 1.0 mmol L-1 ferrioxalate resulted in complete conversion of this herbicide and 70% total organic carbon removal. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: ferrioxalate; tebuthiuron; diuron